قورينا: الحضارة الإغريقية في شرق ليبيا (Comprehensive Journal of Science, 2025)
This study examines the history of the Cyrenaica region during the ancient era, aiming to analyze the foundations upon which the region's civilization was built. It seeks to interpret the factors behind its political and economic independence amidst the conflicts of major imperial powers. The research problem lies in attempting to decouple the cultural dependency on the Greek center from the self-autonomy practiced by Cyrene, and exploring how it transformed the natural monopoly of its resources into a tool for asserting regional sovereignty.The study adopts a historical-analytical approach, utilizing tools of comparative source criticism of classical texts (such as Herodotus and Strabo). These accounts are cross-referenced with archaeological and numismatic evidence (coins) to highlight the role of the local Libyan component in shaping the region's identity.The study concluded with several fundamental results, most notably that the Cyrenaean economy was essentially a rentier economy, relying heavily on the Silphium plant as a sole strategic resource. While this provided the city with immense monetary power, it also rendered it vulnerable to collapse upon the plant's extinction. Furthermore, the study proved that Cyrene's stability was not a product of Hellenic isolation but rather the result of a profound cultural and social synthesis with local Libyan tribes through intermarriage and alliances. This fusion was manifested in the emergence of the Zeus-Ammon cult and the reliance on Libyan expertise in horsemanship.The study recommends the necessity of re-reading the region's history from a local perspective that transcends Hellenocentric narratives. It also emphasizes the importance of archaeological protection for the region's sites and leveraging research findings to enhance cultural tourism.